Clinicopathological features of papillary thyroid carcinoma: A single-centre experience in Turkey - Senel, Fatma (Annals of Medical Research, 2021)
Aim: The goal of this study was to determine the incidence of papillary thyroid carcinoma (PTC) at our centre and examine the clinicopathological features of the tumours.Material and Methods: The study included 823 patients who underwent thyroidectomies in our centre between January 2013 and June 2017 and were examined histopathologically at the Pathology Clinic. We examined their demographic characteristics, preoperative diagnoses, operative procedures, FNAC diagnoses, histopathological characteristics, and postoperative prognoses.Results: Out of the 823 patients, 16.3% were diagnosed with malignancy. Of these diagnoses, 89.6% were papillary carcinomas, 3.7% were follicular carcinomas, 3% were lymphomas, 1.5% was medullary carcinomas, 1.5% were anaplastic carcinomas, and 0.7% were poorly differentiated carcinomas. The rate of PTC incidence in thyroidectomy specimens was 14.6%. In our cases, the multifocality rate of tumours was 31.7%, and the rate of bilateral disease was 24.2%. Neck dissection was performed in 11 PTC patients. Seven of these patients (5.8%) had lymph node metastasis. Of all patients, 46.7% received postoperative radioactive iodine (RAI) therapy. No recurrence or distant metastasis was detected in any of the cases.Conclusion: PTC is the most common type of thyroid carcinoma at our centre. Fine-needle aspiration cytology (FNAC) is valuable for diagnosing classical PTC. Because of the high occurrence of bilateral and multifocal disease in PTC, performing total thyroidectomy is appropriate. Long-term life expectancy is good for these patients.
Keywords: Fine-needle aspiration cytology; papillary thyroid carcinoma; total thyroidectomy